2020
DOI: 10.1021/acs.jafc.0c02971
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes of DNA Methylation Induced by Heat Treatment Were Involved in Ethylene Signal Transmission and Delayed the Postharvest Ripening of Tomato Fruit

Abstract: Deoxyribonucleic acid (DNA) methylation plays an important role in fruit ripening and senescence. Here, the role of DNA methylation of the CpG island of SlACS10, LeCTR1, LeEIN3, LeERT10, and SlERF-A1 genes induced by heat treatment (37 °C) in postharvest ripening of tomato fruit was studied. After heat treatment, the firmness and vitamin C content showed higher levels, the loss of aldehydes in volatile components was delayed, and the activities of methylase and demethylase decreased in tomato fruit. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…The taste of tomato mainly depends on the sugar‐acid ratio, but its unique aroma comes from volatile substances (Pott et al, 2020). Pu et al (2020) found 58 volatile organic compounds (VOCs) during the ripening of tomato fruits. Most of the volatile substances in mature fruits are derived from terpenoid, lipid and carotenoid precursors, or fatty acid and amino acid derivatives (Cheng et al, 2020; Klee & Tieman, 2013).…”
Section: Dna Methylation Regulates the Quality Of Tomato Fruit Ripeningmentioning
confidence: 99%
“…The taste of tomato mainly depends on the sugar‐acid ratio, but its unique aroma comes from volatile substances (Pott et al, 2020). Pu et al (2020) found 58 volatile organic compounds (VOCs) during the ripening of tomato fruits. Most of the volatile substances in mature fruits are derived from terpenoid, lipid and carotenoid precursors, or fatty acid and amino acid derivatives (Cheng et al, 2020; Klee & Tieman, 2013).…”
Section: Dna Methylation Regulates the Quality Of Tomato Fruit Ripeningmentioning
confidence: 99%
“…Evidence had shown that ERN1 encoded downstream targets of EIN3 protein as did ERF1 (Solano et al 1998). Hot water treatment delayed the ripening of tomato fruit, which process accompanies the reduction of the expression level of LeERT10 and increase of methylation level (Pu et al 2020). In the present study, the low temperature treatment enhanced the DNA methylation level of LeERT10 and signi cantly reduced the expression of the LeERT10 gene in tomato fruit (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hot water treatment (HWT) can help reduce the postharvest loss and softening rate of fruits [33]. Moderate heat treatment could maintain the sensory quality of cucumbers [34] reduce freezing damage in kiwifruit [35], and change the expression of ethylene signal transduction genes to inhibit the post-ripening of tomatoes [36]. In contrast to the short-term high-temperature treatment, the treatment conditions in this study included continuous high temperature, and the berries changed more drastically at the level of transcription and metabolic profiles.…”
Section: Discussionmentioning
confidence: 99%